Crossbreeding of Three Iranian Sheep Breeds with Respect to Reproductive, Growth and Carcass Characteristics - Kiyanzad, Mohammad Reza (2002)
In Iran, increasing demand for red meat, caused by increasing human population, pasture limitations and increasing cost of production, has become an impetus for sheep producers to change the system of farming and optimise meat production for more efficient output per unit livestock. One way to achieve the latter goal is by taking advantage of the effect of heterosis from crossbreeding. Twenty seven rams and 473 ewes of three popular breeds of sheep in Iran, namely the Chal, Moghani and Zel, were crossed reciprocally. The reproductive performances of the ewes, and the growth performance, feed conversion ratio and carcass traits of the offspring, under an intensive system of management, were studied. Zel ewes showed higher (P<0.05) overall apparent fertility, reproductivity and productivity compared Chal and Moghani ewes.